2018
DOI: 10.1080/08952841.2018.1419476
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the development of mild cognitive impairment and probable Alzheimer’s disease as predicted by hippocampal volume or white matter hyperintensities

Abstract: This study examined biological sex differences in the development of mild cognitive impairment (MCI) and probable Alzheimer's disease (AD) development as predicted by changes in the hippocampus or white matter hyperintensities. A secondary data analysis of the National Alzheimer's Coordinating Center Uniform Data Set was conducted. We selected samples of participants with normal cognition at baseline who progressed to MCI (n = 483) and those who progressed to probable AD (n = 211) to determine if hippocampal v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 85 publications
(96 reference statements)
4
46
0
1
Order By: Relevance
“…Research has identified gender differences in AD progression (Burke et al, 2018;Nead et al, 2015;Phung et al, 2010), which has been confirmed using rodent models (Carroll e. al., 2010;Munetumo et al, 2015;Woolley, & McEwen, 1992).…”
Section: List Of Tablesmentioning
confidence: 90%
See 4 more Smart Citations
“…Research has identified gender differences in AD progression (Burke et al, 2018;Nead et al, 2015;Phung et al, 2010), which has been confirmed using rodent models (Carroll e. al., 2010;Munetumo et al, 2015;Woolley, & McEwen, 1992).…”
Section: List Of Tablesmentioning
confidence: 90%
“…These differences suggest that males exhibit more abrupt cognitive impairment earlier in life than females but it eventually plateaus. Females; however, exhibit a gradual decline and show worse performances on cognitive tests at later time points in life than males (Burke et al, 2018;Carroll et al, 2010). This study, accordingly, will analyze these gender differences in the development of AD.…”
Section: List Of Tablesmentioning
confidence: 99%
See 3 more Smart Citations